CONSIDERATION REGARDING THE LAW NO 77/2016 IN VIEW OF DECISION OF THE CONSTITUTIONAL COURT NO 623/2016 - Valentin COCEAN (Challenges of the Knowledge Society)
The forced giving in payment regulated by Law no 77/2016 has created a lot of polemics which are not necessarily solved by the Decision of the Constitutional Court. The present study represents an attempt to clarify some of the implications of the Constitutional Court Decision upon the Law no 77/2016.